Association between oral hygiene and head and neck cancer in Brazil - Nayara Fernanda Pereira; Rossana Mendoza López; Tatiana Natasha Toporcov; Cláudia Kliemann Schmerling; Rafael De Cicco; Edgard Michel-Crosato; Maria Gabriela Haye Biazevic (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2020)
ABSTRACT: Introduction: Poor oral hygiene, regular use of mouthwash and absence of visits to the dentist could correspond to potential risk factors for the development of head and neck cancer. Objective: The objective of this study was to determine whether oral hygiene is associated with the occurrence of oral cavity and head and neck cancer in a Brazilian sample. Method: The variables of oral hygiene condition, such as toothbrushing frequency, dental loss, need and use of prosthesis, and regular visit to the dentist in a case-control study were analyzed in patients from five hospitals in the state of São Paulo, Brazil, paired by gender and age, from the multicenter project Genoma do Câncer de Cabeça e Pescoço (GENCAPO). Results: The most frequent malignancies in the 899 patients included were those of the tongue border (11.41%) and tongue base (10.92%). The multivariable statistical analysis found odds ratio values: Brushing once 0.33 (95%CI 0.25 - 0.44); Brushing twice 0.42 (95%CI 0.35 - 0.52); Flossing always 0.19 (95%CI 0.13 - 0.27); Flossing sometimes 0.19 (95%CI 0.15 - 0.24); Bleeding 2.40 (95%CI 1.40 - 4.09); Prosthesis 1.99 (95%CI 1.54 - 2.56); Visiting the dentist 0.29 (95%CI 0.22 - 0.37); Good hygiene 0.21 (95%CI 0.17 - 0.27); Regular hygiene 0.20 (95%CI 0.15 - 0.25); number of missing teeth (6 or more) 3.30 (95%CI 2.67 - 4.08). Conclusion: These data showed that, in the population studied, indicators of good hygiene such as brushing teeth and flossing were protective factors for mouth and head and neck cancer, while bleeding and many missing teeth were risk factors.